Computer Support of Medical Decisions in Ambulatory Care - Vallbona, C.; Schade, C. P.; Moffet, C. L.; Speck, C. D.; Osher, W. J.; Tristan, M. P. (Methods of Information in Medicine, 1975)
Decision makers in health care systems are giving greater emphasis to ambulatory care because of its recognized magnitude (in terms of volume of services rendered) and its potential cost-effectiveness. A challenge to computer scientists is to develop and evaluate computer support systems for ambulatory care professionals at each one of several critical decision points of the care process. These decision points may be at the level of interaction between patient and physician at the time of each encounter, or at the institutional level where the effect is on the setting in which ambulatory care is delivered.Early experiences of computer applications in ambulatory medicine are helping to delineate areas where there is promise of widespread implementation. One of these areas is the computerization of summary ambulatory medical records such as the health-illness profile. This document serves the dual purpose of facilitating medical decisions at the time of each patient encounter, and administrative decisions made by the clinic directors to meet the health needs of the community.
Keywords: Data Bases; Computer Systems; Ambulatory Record; Decision Algorithms; Health-Illness-Profile